Laboratorijski informacijski sistem in povezava s klinikami Kliničnega centra - Jelovšek, Ana Marija (Informatica Medica Slovenica, 2004)
LIS has been developed to process data in the laboratories of KIKKB. The institute elaborates approximately 15.000 analyses daily. The system consists of a network of 70 workstations and 20 analytical instruments. We have also developed two other programs - Hospit for clinics and Paww for dispensaries. Both programs enable ordering analytes to LIS and reviewing their results. Theordering data is executed from a place where it originates, which lowers probability of mistakes and results are immediately accessible after approval.In addition to ordering they enable numerous other possibilities (statistics, comparative analysis, creating patient files, evidence of the material resource consumption). One of both ordering programs is installed on 270 workstations. Both programs are connected to the hospital information system (BIS).
Keywords: Bolnišnice univerzitetne; Clinical Laboratory Information Systems; Hospitals, University; Klinični laboratorij, informacijski sistemi